The History of Architecture, Culture, and Social Dynamics of Lasem Chinatown in the 20th Century - Sulistyaningsih; Ardiningrum, Rafa Athalita; Wipurniwa, Aisyaka Azzahra (Research and Innovation in Social Science Education Journal (RISSEJ), 2025)
This study aims to reconstruct the historical development of Kampung Pecinan Lasem, one of the oldest Chinese settlements in Indonesia, throughout the twentieth century. Although Lasem has long been recognized as an important historical settlement, scholarly discussions have largely focused on Chinatowns in larger urban centers, leaving smaller historical communities such as Lasem relatively underexplored. This research therefore examines the transformation of Kampung Pecinan Lasem through three interconnected dimensions: architectural development, Chinese–Javanese cultural acculturation, and socio-economic dynamics. The study employs the historical method, which includes heuristics through field observations, interviews, and document studies, followed by source criticism, interpretation, and historiography. The findings indicate that the development of Kampung Pecinan Lasem was strongly influenced by major political transitions in Indonesia, from the colonial period and Japanese occupation to the independence revolution and the New Order era. These changes shaped the transformation of architectural forms from traditional Chinese–Javanese structures into hybrid forms incorporating European and modern elements while maintaining symbolic cultural features. Cultural acculturation also occurred in everyday practices such as batik production, religious rituals, language use, and culinary traditions, resulting in the emergence of a distinctive local identity known as “Cina Lasem.” In addition, the settlement played an important socio-economic role as a center of trade and batik production that supported local economic networks involving both Chinese entrepreneurs and Javanese workers. These findings demonstrate that Kampung Pecinan Lasem represents a historically resilient cultural landscape where architectural hybridity, cultural interaction, and economic cooperation enabled the community to adapt to changing political and social conditions throughout the twentieth century.